Informal care for the elderly - Šadl, Zdenka (Družboslovne razprave, 2023)
The article deals with the discrimination of workers who are responsible for caring for elderly family members. Some basic questions emanating from carers’ discrimination in the light of workplace norms, organisational culture, policies for coordinating care and work, the gendered nature of informal eldercare, and anti-discrimination legislation are posed. A review of the literature shows that both female and male carers are exposed to discrimination and that the fundamental sources of discriminatory behaviour include stereotypes of working carers, their taking or requesting of flexible working arrangements and leave to care for a family member, a lack of, or inadequate, work–care reconciliation policies, and deficiencies in the law.
Keywords: discrimination; Diskriminacija; Družina; družinska neformalna oskrba; informal family care; konflikt oskrba-delo; Oskrba starostnikov; oskrbovalci starejših; Trg dela; work-care conflict; working carers; zaposleni oskrbovalci; Zaposleni v storitvenih dejavnostih